ANALISIS PESAN DAKWAH DALAM FILM AIR MATA FATIMAH - Haramain, Genta; Azima, Fauzan; Agusmal, Deni (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
Film a medium communication used for sharing messages information to audience. Message contained in film is very diverse depending on genre film. In Indonesia, one of the film genres that is popular with the audience is religious-themed films. Religious films have information about da'wah messages that can be applied to life. A film called Air Mata Fatimah is based on a true story in social life in Indonesia, from North Sumatra. This film can be interpreted as a da'wah medium that contains demands, learning and guide for the audience. This research was explored qualitative, in the form of a documentation study of film media using Roland Barthes' semiotic theory analysis. The data collection technique is in the form of a document technique by means of screen shooting of scenes from the film script of Air Mata Fatimah, as well as references obtained through articles and journals. The results of this research are in the form of an analysis of da'wah messages conveyed through the characters of each scene in the film Air Mata Fatimah. This film has an implied meaning of the message of da'wah conveyed in the form of moral messages in life. Among them are fighting for the truth and his rights as a Muslim, sincerity, prayer and prayer asking for forgiveness and asking for protection from Allah SWT, and helping each other.